2016
DOI: 10.1002/mren.201500054
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review on Controlled Synthesis of Long-Chain-Branched Polyolefins: Part 2, Multiple Catalyst Systems and Prepolymer Modification

Abstract: Long-chain branching plays an important role in the performance of polyolefi ns (POs). The existence of a very small amount of long-chain branches (LCBs), i.e., <1 per 10 000 carbons, can signifi cantly improve processability of the polyolefi n materials, which is highly desired for those intractable polyolefi ns with narrow molecular weight distribution and high degree of crystallinity. Numerous literatures have been published on the controlled synthesis of long-chain-branched POs. In the previous paper, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 98 publications
0
25
0
Order By: Relevance
“…In the previous two papers of this review series, we have summarized the synthesis of longchain branched POs. [6,7] In this paper, we will give a comprehensive review on the characterization of long-chain branched polymers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the previous two papers of this review series, we have summarized the synthesis of longchain branched POs. [6,7] In this paper, we will give a comprehensive review on the characterization of long-chain branched polymers.…”
Section: Introductionmentioning
confidence: 99%
“…The structural properties of branches include: branch length, branch topology, degree of branching, and M b (average molecular mass between adjacent branching points), with all giving significant effect on the final physical properties of POs. In the previous two papers of this review series, we have summarized the synthesis of long‐chain branched POs . In this paper, we will give a comprehensive review on the characterization of long‐chain branched polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Long-chain branches have been traditionally introduced in polyolefins either by utilizing specialized metallocene catalysts, which are capable of forming macromers and incorporating them, or by combining two catalysts, whereupon one generates macromers from ethylene and the other incorporates them along with the monomer [15,16]. The latter approach can be employed in one reactor, as a tandem catalytic system, or in two sequential reactors, as a cascade polymerization, by which macromers are formed in the first reactor through excessive chain transfer to monomer or β-hydride elimination reactions, and are subsequently incorporated along with monomers in the second reactor by a highly comonomer-selective catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…The latter approach can be employed in one reactor, as a tandem catalytic system, or in two sequential reactors, as a cascade polymerization, by which macromers are formed in the first reactor through excessive chain transfer to monomer or β-hydride elimination reactions, and are subsequently incorporated along with monomers in the second reactor by a highly comonomer-selective catalyst. The low degree of control on the extent and length of long-chain branches in the single catalyst systems hampers the application of the former, while the separation and purification of unreacted macromers and, consequently, the high production cost of the two-catalyst systems suppress the industrial development of the latter [16]. In that sense, the new developments based on the CCTP reaction become more promising [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…LevA and GVL are functionally simpler than the compound classes described earlier and, as a result, are precursors to monomers that are typically derived from petroleum. , LevA is generated through the continued acid-catalyzed transformation of furans, especially HMF, , and formation of GVL from LevA requires an additional reductive catalytic step typically accomplished with a supported ruthenium catalyst. , Several schemes have been developed that use LevA or GVL as starting materials for the synthesis of drop-in replacements to petrochemical monomers. For example, Bond et al demonstrated that butenes can be generated from GVL in high yields (>90% of theoretical molar yield) through catalytic decarboxylation. , Butenes have drop-in potential in polyolefin process streams. This GVL-to-butenes decarboxylation route also can be modified to produce adipic acid ,, and ε-caprolactam, ,,, both of which are commercially relevant in the production of polyamides (e.g., nylon-6 and nylon-6,6, respectively). Finally, new materials derived from the LevA/GVL platform have been reported, including high- T g (>200 °C) α-methylene-γ-valerolactone (MGVL)-based polymers and related polyurethanes. , …”
mentioning
confidence: 99%